Effect of the COVID-19 pandemic on the proportion of physically active children and adults worldwide: A systematic review and meta-analysis - Chaabna, Karima; Chaabane, Sonia; Jithesh, Anupama; Doraiswamy, Sathyanarayanan; Mamtani, Ravinder; Cheema, Sohaila (Frontiers in Public Health, 2022)
Introduction Safety measures implemented to address the COVID-19 pandemic have had a profound impact on the mobility of people worldwide We synthesized the global evidence on physical activity (PA) participation before and during the pandemic. Methods We conducted a systematic review, searching PubMed, Embase, WHO Global literature on coronavirus disease (between January 2020 and April 2022), and reference lists. Meta-analysis and meta-regression were conducted to quantitatively synthesize the data. Results and discussion Sixty-three primary studies were included. In children, the global pooled prevalence of PA was 46.4% before the pandemic, 40.6% during the pandemic before movement restriction (MR), and 19.5% during MR. A statistically significant decrease in prevalence was observed between the period before the pandemic and the period during which MR was implemented (p < 0.001). In adults, the global pooled prevalence (both sexes) decreased between the periods before the pandemic (64.7%) and during MR (57.0%). During the period of COVID-19 MR, children had significantly lower odds to meet the WHO PA recommendation than adults (19.5%, 95%CI: 15.8–23.8% vs. 57.0%, 95%CI: 43.3–62.5%; OR = 0.21; p ≤ 0.001). Patient populations were less active than the general population, and their PA levels decreased during the pandemic. Mental and physical health benefits of PA have been well-demonstrated. Prioritizing PA in health campaigns and strategies is critical to address health issues exacerbated during this pandemic. Protocol registration doi: 10.17605/OSF.IO/GVABX.